2016
DOI: 10.3389/fnhum.2016.00285
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences in the Neural Correlates of Specific and General Autobiographical Memory

Abstract: Autobiographical memory (AM) underlies the formation and temporal continuity over time of personal identity. The few studies on sex-related differences in AM suggest that men and women adopt different cognitive or emotional strategies when retrieving AMs. However, none of the previous works has taken into account the distinction between episodic autobiographical memory (EAM), consisting in the retrieval of specific events by means of mental time travel, and semantic autobiographical memory (SAM), which stores … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 133 publications
1
11
1
Order By: Relevance
“…Our results revealed that East Asians engage regions such as the hippocampus and fusiform more than Americans during the formation of these types of memories at encoding. Taken together, this suggests that engagement of perceptual and memory systems during encoding differ by culture, and our results establish culture as another individual difference like gender (Compère et al, 2016) and aging (Dennis et al, 2008) that can impact neural regions supporting specific memory. Future research should consider whether cultural differences in specific memory reflect differences in perceptual processes related to the use of high versus low spatial frequency information.…”
Section: Discussionsupporting
confidence: 63%
“…Our results revealed that East Asians engage regions such as the hippocampus and fusiform more than Americans during the formation of these types of memories at encoding. Taken together, this suggests that engagement of perceptual and memory systems during encoding differ by culture, and our results establish culture as another individual difference like gender (Compère et al, 2016) and aging (Dennis et al, 2008) that can impact neural regions supporting specific memory. Future research should consider whether cultural differences in specific memory reflect differences in perceptual processes related to the use of high versus low spatial frequency information.…”
Section: Discussionsupporting
confidence: 63%
“…These circuits have been also implicated in sex-specific patterns in cognitive processes relevant to trauma and related psychopathology, including memory, reward processing, and emotional regulation. Semantic memory associates with increased PFC and dorsal ACC (dACC) activations among females as compared to males, suggesting more emotional encoding [39]. Reward-based risk taking involves higher striatal activation in females vs. males [40], and emotional regulation has been found to associate with stronger negative amygdala-PFC connectivity and positive amygdala-insula connectivity among females and with weaker connectivity in these pathways among males [41].…”
Section: Introductionmentioning
confidence: 99%
“…However, using a stricter threshold but not correcting for multiple comparisons (voxel-wise p<0.005, cluster size > 5mm 3 ) revealed bilateral clusters in the dorsal anterior cingulate cortex in the female > male contrast and bilateral superior temporal sulcus, rostral prefrontal cortex and cerebellum, as well as unilateral ventral premotor cortex (Figure 4). The dorsal anterior cingulate cortex may be involved in a sex difference during autobiographical memory processing in humans (Compère et al, 2016).…”
Section: Figure 2 No Differences In Regional Volume (Corrected For Wmentioning
confidence: 99%